2019
DOI: 10.1128/mra.01569-18
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Vibrio mediterranei 117-T6, a Potentially Pathogenic Bacterium Isolated from the Conchocelis of Pyropia spp

Abstract: Vibrio mediterranei is a Gram-negative bacterium of the family Vibrionaceae. Vibrio mediterranei strain 117-T6 was pathogenic to Pyropia yezoensis, a red seaweed cultivated in China, by causing death to its conchocelis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…For Vibrio species, we also analysed the genome location of these T3SS2 gene clusters. In addition to the described chromosomal location of T3SS2 within VPAI-7 of V. parahaemolyticus RIMD2210633 [ 4 ], we identified a T3SS2 gene cluster within the plasmid of a recently sequenced Vibrio mediterranei strain 117-T6 (CP033579) [ 77 ] ( Fig. 5a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Vibrio species, we also analysed the genome location of these T3SS2 gene clusters. In addition to the described chromosomal location of T3SS2 within VPAI-7 of V. parahaemolyticus RIMD2210633 [ 4 ], we identified a T3SS2 gene cluster within the plasmid of a recently sequenced Vibrio mediterranei strain 117-T6 (CP033579) [ 77 ] ( Fig. 5a ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the described chromosomal location of T3SS2 within VPAI-7 of V. parahaemolyticus RIMD2210633 [4], we identified a T3SS2 gene cluster within the plasmid of a recently sequenced Vibrio mediterranei strain 117-T6 (CP033579) [77] (). Another interesting observation was the presence of a T3SS2 gene cluster inserted right next to a T3SS1 gene cluster in Vibrio campbellii strain UMTGB204.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of genome location, in addition to the described chromosomal location of T3SS2 within VPAI-7 of V. parahamolyticus RIMD2210633 [4], we identified a T3SS2 gene cluster within the plasmid of a recently sequenced V. meditteraniae strain 117-T6 (CP033579) [74] ( Fig. 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…It is considered that Pseudomonas, Vibrio or some other bacteria can infect the injured parts of algae, proliferate, and then secrete some degrading material to destroy algal tissue and cause YSD (Wang et al, 2011). Among them, Vibrio mediterranei 117-T6 (Vm 117-T6) has been proved to be a pathogenic bacterium that can cause YSD by Koch's postulates, which can loosen the cellular structures and degrade the contents of Neoporphyra haitanensis (Pyropia haitanensis, before 2020) conchocelis, and even its cells are completely bleached (Liu et al, 2019. It has also been reported that YSD may be caused by the high temperature or continuous rainfall that raises the river water level and carries more organic matter into the seashore (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%